Amkira Tsabo : um estudo sobre a missão educacional metodista junto ao povo kanamari no contexto do estado democrático de direito brasileiro - Figueroa, Ana Claudia (2008)
This dissertation studies the educational actions of the Methodist indigenous mission with the Kanamari people. The Kanamari's relationship characteristics are evaluated, taking into consideration the current state of affairs in which public policies regarding indigenous education, motivated by the characteristics of the democratic rule of law established in the Constitution of the Federal Republic of Brazil promulgated in 1988, are being implemented. This analysis is done through the Methodist Church's indigenous missionary educational practice with the Kanamari tribe. The study is divided into five chapters and organized into two movements. It is done through narrative historiography. In the first movement, comprised of chapters one to three, the introductory elements for understanding the development of the research are presented. These chapters represent elements of existence of the research subjects, of the elements that establish a relationship among themselves from the perspective of indigenous education as public policy. The second movement is made up of the fourth and fifth chapters, which are more analytical of the themes which cross the historicities of the historic subjects that interact in the context of the constitution of the Brazilian democratic rule of law. These chapters represent the most analytical and conclusive part of the research, pointing out transverse elements that aide in the expliciting of conditions of approximation, distancing, partnership and criticism present in the experiences dealt with.